Izzivi inkluzivne vzgoje in izobraževanja za otroke s posebnimi potrebami - Kavkler, Marija (Sodobna pedagogika, 2024)
One of the factors of sustainable and long-term development of education is the development of inclusive education. The goal of inclusive education is to enable all children to be involved, to participate, engage and optimally acquire knowledge, skills and positive attitudes that enable a successful life in society. Slovenia belongs to the countries that implement only one educational program for children with special needs (SEN) in regular educational institutions, which requires minimum standards of knowledge. The implementation of inclusive SEN education is binding with international, EU and national documents therefore we must concentrate on it in Slovenia as well. The paper will present challenges we face in implementing inclusion and the possibilities for improvement. The success of inclusive education into regular educational institutions depends significantly on the dominant discourse. Taking into account the discourse of inclusion for all, the right of all children to inclusive education, which enables educational success, social inclusion and cooperation with peers in the home environment, is at the fore in state policies. However, no country has yet implemented inclusive education for all children with SEN. The discourse of inclusion for some enables inclusion in regular schools for some children with SEN. Researchers are looking for the possibilities of realizing inclusion by combining both discourses in the form of realizable inclusion with the intertwining of the long-term goal of inclusion for all and the quality implementation of inclusion in practice.
Keywords: diskurzi; education; Inkluzivna vzgoja in izobraževanje; pedagogika; pedagogy; praksa; stanje; vzgoja in izobraževanje